Zapowiedź Nowego Przymierza (Jr 31,31-34) w Enarrationes in Psalmos św. Augustyna - Rosik, Mariusz (Verbum Vitae, 2003)
In commenting on the Psalter, St. Augustine refers to Jeremiah's promise of a "new covenant". He gives it its proper interpretation. It is an interpretation done on a literal understanding, however, it also gives a broad sense of the spiritual prophesy of Jeremiah. This was made possible thanks to allegorical (and metaphorical) method used by the Bishop of Hippo, as well as frequent reference to other biblical passages. especialły those written on the pages of the New Testament. For Augustine, the "New Covenant" is a covenant already accomplished in Christ. Access to Him gives faith. Taking advantage of the promises present in Him is possible only to the pure of heart. lt's greatest accomplishment is conduct filled with love. This Covenant has an eternal and universal character.